Leadership for organisational adaptability: How enabling leaders create adaptive space - Jonas Hermann Schulze; Felix Pinkow (Administrative Sciences, 2020)
Organisational adaptability is the ability of an organisation to recognise the need to change and seize opportunities in dynamic environments. In an increasingly complex world, leadership must pay attention to dynamic, distributed, and contextual aspects in order to position their organisations for adaptability. The theory of dynamic capabilities constitutes a central concept for the requirements that enable organisational adaptability. Recent research suggested a model of "leadership for organisational adaptability" embedded in the theory of dynamic capabilities and ambidextrous leadership. This model ascribes leaders the task of creating "adaptive spaces", which are ways to engage in tension that arises when new ideas collide with an organisation's operational system, in order to generate and scale innovation. This work employs a qualitative research design by conducting expert interviews with participants from the management consulting industry as an exemplary object of research, and it identifies ways by which leaders can create such adaptive spaces. Findings indicate that leaders predominantly achieve this by providing employees with head space and opportunities to connect with others and promote diversity within their organisations. However, they could engage more actively in activities that pressure the organisation to change, leverage network structures to scale innovation, and in developing employees. It further emerged that organisations have not fully internalised the notion of distributed leadership, which is deemed crucial for coping with complexity.
Keywords: 350; adaptive organization; adaptive space; ambidexterity; dynamic capabilities; dynamic environment; enabling leadership; innovation; leadership; organizational adaptability; shared leadership